Characteristics and conflicts of interests of public speakers at the Psychopharmacologic Drug and Advisory Committee meetings regarding psychiatric drugs. Issue 4 (4th February 2020) - Roberts, Will; Jellison, Samuel; Wayant, Cole; Vassar, Matt
Abstract : The Psychopharmacologic Drug Advisory Committee (PDAC) is one of 33 advisory committees of the Food and Drug Administration (FDA). During committee meetings, an open public hearing takes place where speakers provide testimonies about the drug in question and are asked, not required, to disclose any conflicts of interests (COIs) before speaking. These speakers may present with COIs which include, but are not limited to, reimbursement for travel and lodging by the pharmaceutical company to attend the meeting; previous or current payments for consulting from the pharmaceutical company and compensation as a paid investigator in previously conducted clinical trials for the drug under review. Our study aimed to investigate the characteristics and COIs of public speakers at PDAC meetings of the FDA. We evaluated 145 public speakers at FDA committee meetings over a 10-year period. We found a total of 52 public speakers disclosed a COI with travel and lodging being the most prominent. Among these speakers, 82.4% provided a positive testimony regarding the psychiatric drug in question. Speakers who had the condition in question were not more likely to provide a positive statement than those who did not. Our results showed that disclosing a COI was associated with increased odds of public speakers providing a favourable testimony for the recommendation of psychiatric drugs. The implications of these findings are concerning since COIs have the potential to skew public speaker's testimonies and persuade committee members to recommend a drug through emotionally charged tactics.